Implementation of School Literacy Movement for Students with Deafness and Mental Retardation - Dita, Anastasia; Martutik, Martutik; Safii, Moh. (Department of Special Education, 2023)
This study aims to describe the implementation of the school literacy movement in students with hearing impairment and mild mental retardation in the Extraordinary High School Putra Pancasila Malang. The research method used is descriptive research with a qualitative approach. The results showed that the implementation of GLS in students with hearing impairment and mild mental retardation at SMALB YP2 Malang was carried out with the interpretation, the organizing, and the application in accordance with the guidebook published by the Ministry of Education and Culture. And learning facilities and activities carried out to support GLS in accordance with the needs of students with each obstacle.